Atributos de negocios para empresas de servicio energético en Colombia (2020)
An energy services company (ESCO) offers its services to private companies, service companies and industries, defining energy efficiency standards. With this idea in mind, the present research aims to propose a set of business attributes of energy service companies applicable to the Colombian market. Methodologically, the project follows a documentary investigation, having carried out a literature review on certain companies in the countries defined by the author in order to be the object of study, considering their policies, models, efficiency, innovation and development. For this particular case, emphasis was placed on the United States, United Kingdom, France, Germany, and China. Attributes were also defined in light of energy supply contracts, energy performance contracts, integrated energy contracts, Chauffage contracts, and facility management. Information was consolidated regarding the alternatives that each country has according to its market under a possible business strategy using strengths and weaknesses. Finally, this final work is expected to serve as an object of discussion for new energy growth alternatives in Colombia.